Estimation of mechanics parameters of rock in consideration of confining pressure using monitoring while drilling data - Zhang, Yonghao; Zhao, Jianbin; Xiao, Zhanshan; Gao, Yanwu; Cui, Shitao; Cheng, Daojie; He, Mingming; Fang, Chaoqiang; Xue, Haifang; Zhao, Ying (Frontiers in Earth Science, 2023)
During the drilling process, high-strength rock can lead to various issues such as drilling suppression, bit wear, and increased operational costs. To ensure safe and efficient drilling operations, it is crucial to accurately predict the strength parameters of the rock and recommend modifications to operational procedures. This paper proposes a low-cost and fast measurement method for predicting the strength parameters of rock in the field. To evaluate the effectiveness of this method, a drilling process monitoring experiment was conducted on sandstone, limestone, and granite. The experiment studied the effect of confining pressure on the response of cutting with an impregnated diamond bit. By analyzing the relationship between the thrust force, torque force, and penetration depth under different confining pressures, the researchers developed an analytical model for drilling that considers confining pressure, compressed crushed zone, and bit geometry. The results show that the confining pressure has a significant effect on the cutting response. As the confining pressure increases, the thrust force, torque force, and penetration depth at the cutting point also increase. Furthermore, a new measurement method was proposed to determine the strength parameters, such as cohesion, internal friction angle, and unconfined compressive strength. The estimated strength parameters for the three rock types using the drilling method were in good agreement with those of the standard laboratory test, with an error range of 10%. This proposed method for estimating rock strength parameters is a practical tool for engineers, providing high-resolution and continuous measurements in the field.